2015
DOI: 10.1111/geoj.12141
|View full text |Cite
|
Sign up to set email alerts
|

Indexing livelihood vulnerability to the effects of typhoons in indigenous communities in Taiwan

Abstract: The theoretical importance of understanding how livelihoods shape local vulnerability to the effects of climate change has received broad attention, but with relatively few attempts to produce and implement an analytical framework based on the theory. This study develops a livelihood vulnerability analytical framework, and applies it to the case of rural indigenous communities of Taiwan that are regularly exposed to typhoons and associated geological hazards. Measures of the factors influencing how typhoons im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…2016), the FORIN approach provides a mechanism for the comparison of findings from disparate case studies. For example, Lin and Polsky (, this volume) provide an interesting case study quantifying livelihood vulnerability in Taiwan, especially in indigenous populations. They were able to identify different indigenous communities in terms of their three dimensions of vulnerability (using the climate change adaptation definition)—sensitivity, exposure and adaptive capacity—with respect to typhoon hazards, using an historical lens.…”
Section: Examining Root Causesmentioning
confidence: 99%
“…2016), the FORIN approach provides a mechanism for the comparison of findings from disparate case studies. For example, Lin and Polsky (, this volume) provide an interesting case study quantifying livelihood vulnerability in Taiwan, especially in indigenous populations. They were able to identify different indigenous communities in terms of their three dimensions of vulnerability (using the climate change adaptation definition)—sensitivity, exposure and adaptive capacity—with respect to typhoon hazards, using an historical lens.…”
Section: Examining Root Causesmentioning
confidence: 99%
“…There are at least two important benefits of using such index. First, the index contributes to the operationalisation of vulnerability theory by taking into account the interdependencies between global stressors and local assets and mechanisms (Lin and Polsky, 2015). An index-based approach can be useful to understand both the impacts and the social capabilities for anticipatory or reactive modes (adaptive capacities) to reduce farmers' sensitivity and exposure to exogenous threats (Eakin and Bojórquez-Tapia, 2008;Hahn et al, 2009;Lin and Polsky, 2015).…”
Section: Trade-off Between Sensitivity and Adaptive Capacitymentioning
confidence: 99%
“…The five components have similarities to the Livelihood Vulnerability Index developed by [34] but lacks climate change variability component. A recent study by [35] attempted to formulate a livelihood vulnerability analytical framework incorporating climate change vulnerability factors such as sensitivity and adaptation capacity. The study revealed that the most vulnerable communities are those who are poor and within the vulnerability loops.…”
Section: Sustainable Livelihoodmentioning
confidence: 99%